Religiosity and Attitudes toward Suicide Among Filipinos - Reyes, Marc Eric S.; Daluping, Therese Angelie C.; Dela Cruz, Omar Joseph SJ.; Estremadura, Sigmund Gabriel A.; Gavino, Jonah Emmanuel D.; Villanueva, Elaine G.; Jacob, Alvin L., III (UI Scholars Hub, 2025)
Religiosity is generally negatively associated with attitudes toward suicide. Religious individuals typically have more negative attitudes toward suicide than individuals with lower levels of religiosity. This is partly due to the belief that suicide goes against many religious teachings that revere life as a sacred gift from God. Hence, using a cross-sectional, predictive design, we aimed to investigate the link between religiosity and suicide attitudes and how much religiosity predicts different suicide attitudes. Using non-probability convenience sampling, 1148 Filipino participants aged 18–65 completed an online test battery: Centrality of Religiosity Scale Interreligious form-20 and Attitudes Toward Suicide Scale. Results revealed that religiosity is significantly associated with and predicts eight suicide-related attitudes, namely, suicide as a right, incomprehensibility, preventability, tabooing, normal-common, suicidal process, preparedness to prevent, and resignation. These results indicate that religiosity primarily negatively predicts certain attitudes toward suicide among Filipinos. Our findings reveal the critical role that religiosity plays in Filipinos' attitudes toward suicide, which may have significant implications for preventing and understanding suicidality in the Philippines.